Correspondance entre François Laydevant et Albert Perbal, 1927-1952 : dialogue du missionnaire et du missiologue - Laydevant, François. (Studies in Christian Mission, 1994)
This volume presents the 25 years correspondence of a Roman Catholic missionary, Fr. François Laydevant, who worked in Lesotho from 1905 to 1954, with a Roman Catholic missiologist, Fr. Albert Perbal, based in Rome, Italy. The exchange of letters was provoked by the missiologist who needed direct information from the mission field for his own research and teaching, and first of all in order to fulfil his role of consultant with the Institute for the Study of African Languages and Cultures in London and the Conference Romaine des Missions Catholiques d'Afrique in Rome. The main result of the correspondence, apart from fulfilling the above stated purpose, was to propel Fr. Laydevant into fruitful anthropological, ethnological and historical research into Lesotho and its people. The correspondence deals with many contemporary missiological problems of the time. It is also a primary source for the history of the Church in Lesotho, in particular the Roman Catholic Church. FRENCH TEXT Ce volume comprend la correspondance de vingt-cinq ans d'un missionnaire catholique, le Père François Laydevant, qui travailla au Lesotho de 1905 à 1954, avec un missiologue catholique, le Père Albert Perbal, qui demeurait à Rome. C'est le missiologue qui provoqua l'échange de lettres. Il avait besoin d'information directe à partir du champ missionnaire pour ses recherches et son enseignement et d'abord pour remplir son rôle auprès de l'Institut pour l'Étude des langues et des Cultures Africaines à Londres et auprès de la Conférence Romaine des Missions Catholiques d'Afrique à Rome. Le résultat le plus évident de cette correspondance fut de lancer le Père Laydevant dans les recherches ethnologiques, anthropologiques et historiques sur le Lesotho et son peuple. La correspondance aborde plusieurs questions missiologiques contemporaines au cours de ces 25 ans et demeure une source primaire pour l'histoire de l'Église au Lesotho, en particulier l'Église Catholique.